Adaptive fuzzy integral sliding mode pressure control for cutter feeding system of trench cutter - Tian, Qi-yan; Wei, Jian-hua; Fang, Jin-hui; Guo, Kai (Journal of Central South University, 2016)
A nonlinear pressure controller was presented to track desired feeding pressure for the cutter feeding system (CFS) of trench cutter (TC) in the presence of unknown external disturbances. The feeding pressure control of CFS is subjected to unknown load characteristics of rock or soil; in addition, the geological condition is time-varying. Due to the complex load characteristics of rock or soil, the feeding velocity of TC is related to geological conditions. What is worse, its dynamic model is subjected to uncertainties and its function is unknown. To deal with the particular characteristics of CFS, a novel adaptive fuzzy integral sliding mode control (AFISMC) was designed for feeding pressure control of CFS, which combines the robust characteristics of an integral sliding mode controller and the adaptive adjusting characteristics of an adaptive fuzzy controller. The AFISMC feeding pressure controller is synthesized using the backstepping technique. The stability of the overall closed-loop system consisting of the adaptive fuzzy inference system, integral sliding mode controller and the cutter feeding system is proved using Lyapunov theory. Experiments are conducted on a TC test bench with the AFISMC under different operating conditions. The experimental results demonstrate that the proposed AFISMC feeding pressure controller for CFS gives a superior and robust pressure tracking performance with maximum pressure tracking error within ±0.3 MPa.